2019
DOI: 10.1002/bjs5.50149
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the association of extraintestinal manifestations with the development of pouchitis in patients with ulcerative colitis

Abstract: Background The presence of extraintestinal manifestations may be associated with the development of pouchitis in patients with ulcerative colitis after ileal pouch–anal anastomosis. The aim of this study was to assess this correlation. Methods A systematic literature search was performed using MEDLINE and the Cochrane Library. Studies published in English up to 22 May 2017 investigating the association between extraintestinal manifestations and development of pouchitis in adults with ulcerative colitis were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
1
9
1
Order By: Relevance
“…In bivariate analysis, patients with CD of the pouch were more likely to demonstrate extraintestinal manifestations when compared to patients without a history of pouchitis. A recent meta-analysis indicated that the presence of extraintestinal manifestations was associated with a significant increase in risk of developing both acute and overall pouchitis, 20 however our study demonstrated an increased association with extraintestinal manifestations in the CD of the pouch group alone. Patients with no pouchitis were significantly more likely to demonstrate dysplasia at the time of colectomy when compared to patients with CD of the pouch and chronic pouchitis.…”
Section: Discussioncontrasting
confidence: 95%
“…In bivariate analysis, patients with CD of the pouch were more likely to demonstrate extraintestinal manifestations when compared to patients without a history of pouchitis. A recent meta-analysis indicated that the presence of extraintestinal manifestations was associated with a significant increase in risk of developing both acute and overall pouchitis, 20 however our study demonstrated an increased association with extraintestinal manifestations in the CD of the pouch group alone. Patients with no pouchitis were significantly more likely to demonstrate dysplasia at the time of colectomy when compared to patients with CD of the pouch and chronic pouchitis.…”
Section: Discussioncontrasting
confidence: 95%
“…A specific IL-1B gene polymorphism (rs1143627; TT genotype) was statistically significantly associated with the development of both overall and chronic pouchitis in our cohort and may be a predictive factor for the future development of pouchitis. The presence of EIM, which was shown to have an association in our previous metaanalysis [24], was another predictive factor for the development of both overall and chronic pouchitis. This association was consistently observed in our previous cohorts [16,25] and was also observed in the present cohort.…”
Section: Discussionmentioning
confidence: 61%
“…Patients may present with extraintestinal manifestations such as arthralgia, and this can aid diagnosis of primary idiopathic pouchitis [40]. There may be an association between PSC and pouchitis [40].…”
Section: Causes Of the Pouch Behaving Badlymentioning
confidence: 99%
“…Patients may present with extraintestinal manifestations such as arthralgia, and this can aid diagnosis of primary idiopathic pouchitis [40]. There may be an association between PSC and pouchitis [40]. Other points to note in the history include if the patient is a nonsmoker [41], use of nonsteroidal anti‐inflammatory drugs (NSAIDs) [41,42] and previous extensive colonic disease [42].…”
Section: Causes Of the Pouch Behaving Badlymentioning
confidence: 99%